Produtividade, qualidade e crescimento de cultivares de batata destinadas à indústria sob doses de nitrogênio - Tamanini Junior, Cleto (2019)
The majority of the cultivars for industry used in Brazil are from abroad, however, breeding programs have developed national cultivars for this purpose, being important to study if the fertilizer management affects cultivars of different origins. The objective of this work was to evaluate the yield, quality and growth of two potato cultivars for industry, submitted to four doses of nitrogen. Three field trials were conducted between December 2015 and April 2018, with eight treatments in a randomized block design (RBD) in a factorial scheme with two cultivars (Atlantic and BRSIPR Bel) and four nitrogen doses (0, 75, 150 and 225 kg ha-1) with four replicates. The spacing was 0.8 m between rows and 0.25 m between plants, the hilling was performed around 28 days after planting (DAP). Two evaluations of the morphology and growth of the cultivars were carried out at 42 and 63 DAP in 2018, whereas at harvest tuber yields and its components were evaluated in all three years. For the quality measurements, we quantified the dry matter content and the oil absorbed by the chips in all three years. For all the variables studied in the present study, there was no interaction between cultivar and dose, therefore nitrogen management could be similar for both Atlantic (foreign) and BRSIPR Bel (national) cultivars. In the comparison between cultivars, BRSIPR Bel presents higher total and commercial yield due to its greater number of tubers, mostly in the range of 100 to 200 g. However, Atlantic cultivar presents a higher percentage of dry matter in the tubers, providing better quality in the frying, with less absorption of oil. The most relevant morphological characteristics for BRSIPR Bel which result in higher yield were the number of main stems, number of tubers initiated and leaf area index. For the tubers formed by Atlantic, greater number, fresh and dry matter were observed, this cultivar filled tubers earlier, with greater accumulation of photoassimilates. It is concluded that BRSIPR Bel has higher yield and Atlantic has tubers of higher quality. For nitrogen doses, the best dose was 151 kg ha-1 for the highest commercial yield of 34 t ha-1.